Aplicações da q-Álgebra em física da matéria condensada - Marinho, André Afonso Araújo (2014)
We address the generalization of thermodynamic quantity q-deformed by q-algebra that describes a general algebra for bosons and fermions . The motivation for our study stems from an interest to strengthen our initial ideas, and a possible experimental application. On our journey, we met a generalization of the recently proposed formalism of the q-calculus, which is the application of a generalized sequence described by two parameters deformation positive real independent and q1 and q2, known for Fibonacci oscillators . We apply the wellknown problem of Landau diamagnetism immersed in a space D-dimensional, which still generates good discussions by its nature, and dependence with the number of dimensions D, enables us future extend its application to systems extra-dimensional, such as Modern Cosmology, Particle Physics and String Theory. We compare our results with some experimentally obtained performing major equity. We also use the formalism of the oscillators to Einstein and Debye solid, strengthening the interpretation of the q-deformation acting as a factor of disturbance or impurity in a given system, modifying the properties of the same. Our results show that the insertion of two parameters of disorder, allowed a wider range of adjustment , i.e., enabling change only the desired property, e.g., the thermal conductivity of a same element without the waste essence